The Immigration Policy in the Law of the European Union - A. O. Yumatova (Московский журнал международного права, 2008)
The development of the international economy is closely related to the immigration process. The European Union is an significant member of the world policy, thus studying the immigration in the frame of the European Union is very important. The article “The immigration policy in the law of the European Union” is devoted to the analysis of the law development of the immigration process in the European Union. The attention is paid to the law progress and the main stages of its development. The author of the article bases her research on the international law sources showing the continuity in solutions of the immigration issues in the European area Attention is paid to the spread of immigration and motives of its origination. Studying the immigration policy the author comes to the conclusion that not all the European Union states pay sufficient attention to this question and tend to use cheap work-force in their economies. In the author’s opinion it is necessary to cooperate for the stability and solving main problems in the immigration policy sphere of the European Community.